Emotional Neuroscience and Academic Achievement: Current Trends and Perspectives - Aroutzidis, Anthimos; Antonopoulou, Hera (Technium Social Sciences Journal, 2025)
This paper approaches the intersection of emotional neuroscience with academic achievement, placing a strong emphasis on the critical role emotions play in learning. It challenges the traditional view of emotions in education and points out the need for understanding and measuring emotional biology in creating brain-friendly learning environments. Combining the theoretical frameworks, the discussion draws a link between emotional neuroscience and academic success by highlighting neurobiological foundations, emotional regulation, stress, anxiety, and neuroplasticity. Most importantly, it explains the role of emotional intelligence and how this ability creates a positive impact on cognitive functioning and academic outcomes. This paper pushes the issue of multidimensionality in education and neuroscientific knowledge to nurture emotional well-being and bring about greater academic achievement. It reflects on innovative interventions and leading-edge innovations in education that can shape schools into emotionally supportive learning environments. The conclusion calls for interdisciplinary collaboration to change educational practices. The paper supports its arguments with an extensive bibliography in the areas of cognitive neuroscience, emotional intelligence, academic achievement, and mental health research.